Proposing and developing Qaf online system for Quranic contests - Abdo Khaled, Nashwan; Abdulghafor, Rawad Abdulkhaleq Abdulmolla; Al-Aghbari, Mohammed; Chamie, Marhaf; Zaid, Mohammed (Design for Scientific Renaissance, 2019)
Muroja’ah is reciting Quran verse (ayat) in order to recall the verses that have been memorized. This activity is necessary for people who memorizes Quran (in whole or in part). Muroja'ah is better performed in front of a teacher or companion in order to obtain feedbacks and evaluations, but some people might not be able to find one due to some reasons. A mobile application using Automatic Speech Recognition (ASR) to recognize Quran recitation can be used as an alternative to replace a teacher’s or companion’s role in assisting muroja’ah. Currently, some Quran mobile applications using ASR are available, but none of these is suitable to be used for assisting muroja’ah. Therefore, a new mobile application using ASR for assisting muroja’ah - named Rafiqul Huffazh - is developed in this project. The main feature of Rafiqul Huffazh is to transcribe Quran recitation of user memorization, evaluate the transcription based on the type of error defined and calculate the user score in performing muroja’ah. The application back-end used to transcribe Quran recitation is also developed in this project. The application has passed all the functional testing. Usability testing has also been done and it is concluded that the application interaction is considered suitable for assisting muroja'ah, however its appearance and interaction need further development in order to be more user friendly.